"It doesn't make me any less Aboriginal": The complex politics of translocal place‐making for Indigenous tertiary student migrants. Issue 3 (22nd August 2018) - Harris, Desiree; Prout Quicke, Sarah
Abstract: Indigenous migratory practices have never been comfortably explained using deterministic theories of migration. In this paper, we argue that translocalism offers new hopeful possibilities for building more robust and nuanced understandings of Indigenous migration and for extending theorisations of translocality in postcolonial settler‐states. Drawing on empirical evidence from a small‐scale exploratory study of Indigenous adults who migrated from rural/remote Australia, to Perth, Western Australia, to study at a university, we suggest that a particular politics of place‐making characterises Indigenous translocal subjectivities in settler states. These politics are evidenced by the ways in which the very act of movement from rural/remote areas to large cities for education can draw the authenticity of Indigenous identities into contestation. It also speaks to the resultant importance of translocal networks and places that provide relational spaces to share experiences of, and respond to, these contestations. The participants in this study made use of Indigenous student centres at their universities to develop a sense of place, build translocal networks, nurture their cultural identities, and contest settler assumptions that situate "authentic" Indigenous identities in a remote wilderness past.